Nutrigenomics in Livestock Nutrition: A Pathway to Enhanced Animal Health and Productivity - , D. Chandaka; R.K. Swain; P. K. Regulagadda; U. Chandaka; H. Mekapothula; S. Salur (Indian Journal of Animal Nutrition, 2024)
Nutrigenomics represent emerging discipline that scrutinizes the intricate relationship between diet and genetic expression. These fields investigate how bioactive compounds in food influence gene expression and ultimately impact animal and human metabolism. In livestock, the study of nutrigenomics is constrained by high costs, long generational distances, and ethical considerations. Recent research in livestock nutrigenomics has primarily focused on elucidating the effects of dietary modifications on breeding efficiency, production traits, and animal health. By integrating disciplines such as nutrition, molecular biology, genomics, bioinformatics, molecular medicine, and epidemiology, nutrigenomics aims to elucidate the epigenetic mechanisms underlying disease occurrence. This review provides a comprehensive overview of nutrigenomics, highlighting its significance in understanding the interaction between diet and gene expression in livestock. By deciphering the intricate molecular pathways involved, nutrigenomics holds promise for personalized nutrition strategies tailored to individual genotypes, ultimately improving health outcomes for animals.